2017
DOI: 10.17221/50/2016-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of combining ability in ornamental sunflower for floral and morphological traits

Abstract: Cvejić S., Jocić S., Mladenović E., Jocković M., Miladinović D., Imerovski I., Dimitrijević A. (2017): Evaluation of combining ability in ornamental sunflower for floral and morphological traits. Czech J. Genet. Plant Breed., 53: 83−88.Ornamental sunflowers are widely cultivated for use as cut flowers and/or as garden plants. The objective of the study was to investigate breeding values of new F 1 ornamental sunflower hybrids using incomplete diallel crossing of four ornamental inbred lines: Heliopa, Talia, Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…While, Rf8 was the best general combiner for plant height and seed oil content %. These results were in accordance with the findings of Azab et al(2014); Imran et al(2015); Memon et al(2015); Vikas et al(2017); Cvejic et al(2017); Biradar et al(2018), Bhoite et al(2018), Singh et al (2018), Telangre et al(2019), Haddadan et al (2020) and Rizwan et al, (2020) .…”
Section: General Combining Ability Effectssupporting
confidence: 89%
See 1 more Smart Citation
“…While, Rf8 was the best general combiner for plant height and seed oil content %. These results were in accordance with the findings of Azab et al(2014); Imran et al(2015); Memon et al(2015); Vikas et al(2017); Cvejic et al(2017); Biradar et al(2018), Bhoite et al(2018), Singh et al (2018), Telangre et al(2019), Haddadan et al (2020) and Rizwan et al, (2020) .…”
Section: General Combining Ability Effectssupporting
confidence: 89%
“…The hybrid (A15 x Rf8) exhibited maximum positive heterotic effect (3.25%), along with 40.18 mean seed oil percentage. Similar results were obtained by Tan (2010), Hladni et al (2011), Azab et al (2014, Encheva et al (2015), Ingle et al (2015), Cvejic et al(2017), Vikas et al (2017), Bhoite et al (2018) Abd ElHadi et al(2019, Khan et al (2019), andHaddadan et al (2020) .They indicated that heterosis was manifested in yield crosses for many studied traits.…”
Section: Seed Oil Content%supporting
confidence: 71%
“…The criteria for the global cut flower trade are good plant growth, the maximum number of flowers, coupled with a good stem length and flower size (Nair et al 2002;Gurav et al 2005). There are some important fac-tors that affect the cut sunflower marketability: the diameter of the inflorescence and length of the stem (Cvejić et al 2017).Two types of sunflower varieties are used for the cut flower market. The first type is a single-stem sunflower that tolerates dense planting.…”
mentioning
confidence: 99%
“…Line A-6 (3.337) exhibited highly significant positive GCA effects, which is desirable for OC. The tester A-8 (0.862) exhibited significantly positive GCA effects for OC (Cvejić et al, 2017). Line A-4 (1.238) exhibited significantly positive GCA effects for the desirable PC.…”
Section: Resultsmentioning
confidence: 98%